2005
DOI: 10.3989/scimar.2005.69n3347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changing seawater temperature on photosynthesis and calcification in the scleractinian coral <i>Galaxea fascicularis</i>, measured with O<sub>2</sub>, Ca<sup>2+</sup> and pH microsensors

Abstract: SUMMARY: Single polyps of Galaxea fascicularis were fixed to glass vials with underwater epoxy resin. After regeneration into microcolonies they were used for microsensor measurements of photosynthesis and calcification under different incubating temperatures. Gross photosynthesis was found highest at temperatures of 23 and 26ºC (ca. 0.022 mole O 2 m -3 s -1 ), close to the ambient temperature (i.e. 26ºC). At 35°C, gross photosynthesis was irreversibly inhibited as the microcolonies bleached. The net photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…Studies have shown that while calcification is enhanced as temperature increases, once an optimum value (typically a few degrees below the seasonal maximum temperature) is exceeded, calcification rates rapidly decline (Al-Horani, 2005;Cantin and Lough, 2014). If this warming continues it will ultimately lead to corals ejecting their symbiont dinoflagellates (zooxanthellae), a process known as coral bleaching, which in many cases can lead to coral death (McClanahan et al, 2007).…”
Section: Potential Impacts On the Marine Environmentmentioning
confidence: 99%
“…Studies have shown that while calcification is enhanced as temperature increases, once an optimum value (typically a few degrees below the seasonal maximum temperature) is exceeded, calcification rates rapidly decline (Al-Horani, 2005;Cantin and Lough, 2014). If this warming continues it will ultimately lead to corals ejecting their symbiont dinoflagellates (zooxanthellae), a process known as coral bleaching, which in many cases can lead to coral death (McClanahan et al, 2007).…”
Section: Potential Impacts On the Marine Environmentmentioning
confidence: 99%
“…Fig. 4 shows the fit of the adapted range (α) functional form to the experimental measurements of calcification rate (Al-Horani, 2005). Other researchers have modelled the temperature response of corals with cubic polynomials (e.g.…”
Section: The Adapted Temperature Response (α)mentioning
confidence: 99%
“…Experimental studies have shown that maximum calcification rates occur at an optimum temperature that is 2-3 • C below the maximum temperature (Marshall and Clode, 2004) and that their calcification decreases more rapidly for warming above the optimum than for cooling. If the warming continues, the calcification rate continues to decline, ceasing at a temperature that is typically a few degrees above the seasonal maximum (Al-Horani, 2005;Cooper et al, 2008;Cantin et al, 2010). If the temperature exceeds this threshold, the corals lose their dinoflagellate symbiont, zooxanthellae, in a process known as thermal bleaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this happens, some oxygen ceases to play a normal role in photosynthesis and becomes chemically active as oxygen 'radicals' causing cellular distress. As oxygen radicals become toxic, the zooxanthellae that produce them are expelled by the corals even though this action too puts the corals at risk [32,33] In the reef slope zone, the light was limiting factor for corals as optimal light intensity decreases. Light controls productivity, physiology, and ecology of corals.…”
Section: Abundancementioning
confidence: 99%